Developing an international network for clinical research: the European Cystic Fibrosis Society –– Clinical Trials Network experience. (June 2011) - Bulteel, Veerle; Castellani, Carlo; Conway, Steven P; Dubois, Christine; Fajac, Isabelle; Pereira, Luisa; Reimann, Andreas LG; Boeck, Kris De
Clinical trial networks provide a centralized resource for the successful execution of a clinical trial. For diseases with relatively small populations, such as cystic fibrosis, the most appropriate action is to form a larger operational group. The rationale for setting up a European Clinical Trials Network for cystic fibrosis is to bring new medications to the patients faster. A centralized protocol review will improve the quality and feasibility of clinical studies. Standardization of outcome parameters will help to decrease variation of results and therefore the sample size needed. Motivating patients to take part in research and promoting the safety of participants in clinical trials are of great importance.